2004
DOI: 10.1160/th03-09-0577
|View full text |Cite
|
Sign up to set email alerts
|

Use of soluble fibrin antigen instead of D-dimer as fibrin-related marker may enhance the prognostic power of the ISTH overt DIC score

Abstract: The overt DIC score of the DIC subcommittee of the ISTH includes a fibrin-related marker (FRM) as indicator of intravascular fibrin formation. The type of marker to be used has not been specified, but D-dimer antigen, or fibrin degradation products are used by most investigators. Soluble fibrin complexes have been suggested as more specific indicators of acute intravascular fibrin formation. The aim of the present study was to compare the predictive value of the overt DIC score concerning clinical outcome in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(27 citation statements)
references
References 22 publications
(21 reference statements)
1
26
0
Order By: Relevance
“…Studies have also attempted to define D-dimer cutoff levels. One approach assigned scores for moderate and strong increases on 25% and 75% quartiles derived from over 1000 samples in intensive care [12]. Dempfle et al [12] found this to be approximately 1 lg mL )1 and approximately 3 lg mL…”
Section: Resultsmentioning
confidence: 99%
“…Studies have also attempted to define D-dimer cutoff levels. One approach assigned scores for moderate and strong increases on 25% and 75% quartiles derived from over 1000 samples in intensive care [12]. Dempfle et al [12] found this to be approximately 1 lg mL )1 and approximately 3 lg mL…”
Section: Resultsmentioning
confidence: 99%
“…In fact, many authors found the increase in D-dimers to be a very sensitive marker of fi brinolytic activity following the formation of fi brin. Some authors suggest that the primary site of increased fi brinolytic activity may be the placental uterine interface, while the elevated levels are due to localized increase in fi brin formation (14,15,16). Variations in protein C activity and levels of antithrombin III were not signifi cant.…”
Section: Discussionmentioning
confidence: 99%
“…These laboratory criteria for calculating the overt DIC score included a platelet count, a fibrin-related marker, prothrombin time (PT), and fibrinogen. A recent study showed that the DIC scoring system was sufficiently accurate to make or reject a diagnosis of DIC [3] and soluble fibrin antigen improved the prognostic power of the DIC score [4]. …”
Section: Introductionmentioning
confidence: 99%